Исследование процесса совместимости некоторых полимерных компонентов трехслойной антикоррозионной защитной системы для магистральных газопроводов - Тихомирова, Татьяна Сергеевна; Рассоха, Алексей Николаевич (НТУ "ХПИ", 2006)
У статті наведено результати аналізу процессу суміщення полімерів (полівінілацеталей, сополімеру етилену з вінілацетатом, епоксидного полімеру), що дає змогу оцінити можливість використання обраних полімерних матеріалів у складі багатошарових композиції, які застосовуються для антикорозійного захисту магістральних газопроводів.

The results of the overlap process analyses of polymer materials (polyvynilacetals, copolymer of ethylene with vynilacetate, epoxy) are given in the article. These results can be used for the evaluation of the possibility of overlapping such polymer materials in the multilayer compositions. Such compositions are used for the anticorrosive protection of main gas pipelines.
Keywords: сополимер этилена с винилацетатом; поливинилбутираль; поливинилформаль; термодинамическое взаимодействие; термодинамическая совместимость; антикоррозионная полимерная система; полимерные материалы